Multi-Minicore and Central Core Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
A genome-wide screening was conducted in a consanguinous Algerian family with 3 children with multicore disease at the Groupe Hospitalier Pitie-Salpetriere, Paris, France, and other centers.